Một vài mô hình nạp ngũ hành cho các cặp can chi - Lân, Lê Thành (Journal of Computer Science and Cybernetics, 2016)
In ancient books are shown two mathematical models that attribute of  five elements to the pairs of selestial stems and terrestrial branches. So it might be said that what was done by our ancestors were well-grounded. Our forefathers did not act in an pure empirical and  arbitrary way. Here we set forth this new mathematical model: the five tones are attributed first to the pairs of selestial stems and terrestrial branches, and  the five elements are then attributed to five tones H = H(Aq) = H(A(anim)). The element is denoted here by H, the tone by A, the selestial stem by a, and the terrestrial brach by i. This method attraches importance to the  origin of the problem and that is why the mathematical model is simple. The numerical codes are likewise simple and may be rational interpreted. Using the mathematical graph of congruence, we draw out from this model a table showing the five elements being attributed to the pairs of celestial stems and terrestrial branches in the form of a fine, handy diagonal matrix which is easily commited to memory.